Ethnic minority concentration: A source of productivity growth for Italian provinces?*. Issue 1 (11th October 2017) - Michelangeli, Alessandra; Pontarollo, Nicola; Vittucci Marzetti, Giuseppe
Abstract: This paper aims at assessing the contribution of ethnic minorities to the (total and sectoral) productivity of Italian provinces. We consider the first ten nationalities by numbers of legal immigrants at the provincial level (NUTS 3) 2003–2011. We estimate a spatial panel model to capture both direct and indirect effects of foreign communities on local productivity at the province level, accounting for spatial spillovers. Our findings show that two communities out of the ten considered have a direct positive impact on aggregate labour productivity. Other foreign groups have significant indirect effects: these groups do not affect productivity of provinces where they live, but mainly of the neighbouring provinces, likely because of commuting.